Criminal for Leaking Administs Data of PDDIKTI and PSD-PTU According to Law Number 19 Year 2016 Concerning ITE - Junaedi; Tri Gustaf Said; Muhammad Tahir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Protection for every citizen wherever they are is an obligation that must be fulfilled by a country. This is in accordance with the Preamble to the 1945 Constitution of the Republic of Indonesia in the 4th (fourth) paragraph. One form of recognition, guarantee, protection, and fair legal certainty as well as equal treatment before the law is the existence of adequate arrangements that are very close between the protection of confidential data from individual PDDikti admins and PSD-PTU a Lecturer, both at universities State Universities (PTN) and Private Universities (PTS). Private secrecy is very essential, especially related to the PDDikti and PSD-PTU data of a Lecturer, both at State Universities (PTN) and Private Universities (PTS), because that is where there are individual rights that must be protected by the State. The protection of personal data in the digital era has been regulated and stated in the form of Ministerial Regulation (Permen) No. 20 of 2016 concerning Personal Data Protection (PDP) stipulated November 7, 2016, promulgated and effective since December 1, 2016. The regulation states that Personal Data is data certain individuals who are kept, cared for, and the truth is protected and their confidentiality is protected because that is where there are individual rights that must be protected by the State which should be kept secret except for the interests of the State.